2009
DOI: 10.1007/s00018-009-0196-y
|View full text |Cite
|
Sign up to set email alerts
|

Anti-adipogenesis by 6-thioinosine is mediated by downregulation of PPAR γ through JNK-dependent upregulation of iNOS

Abstract: Adipocyte dysfunction is associated with the development of obesity. This study shows that 6-thioinosine inhibits adipocyte differentiation. The mRNA levels of PPAR gamma and C/EBPalpha, but not C/EBPbeta and delta, were reduced by 6-thioinosine. Moreover, the mRNA levels of PPAR gamma target genes (LPL, CD36, aP2, and LXRalpha) were down-regulated by 6-thioinosine. We also demonstrated that 6-thioinosine inhibits the transactivation activity and the mRNA level of PPAR gamma. Additionally, attempts to elucidat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 51 publications
0
10
0
Order By: Relevance
“…Several studies have reported that JNK activity is specifically required for the initial stage of differentiation events of adipocytes and may act with a positive impact in adipogenesis differentiation [ 34 , 35 ]. Conversely, results from other studies have suggested that JNK activity may have the opposite effect on adipogenesis [ 36 38 ]. In our study, we found that, in both adipogenic and osteogenic differentiation processes, NO increased the phosphorylation of JNK/MAPK, and then p-JNK transportation to the nucleus induced the expression of osteogenic transcription factors and repressed the expression of adipogenic transcription factors, thus increasing osteogenesis and reducing adipogenesis.…”
Section: Discussionmentioning
confidence: 89%
“…Several studies have reported that JNK activity is specifically required for the initial stage of differentiation events of adipocytes and may act with a positive impact in adipogenesis differentiation [ 34 , 35 ]. Conversely, results from other studies have suggested that JNK activity may have the opposite effect on adipogenesis [ 36 38 ]. In our study, we found that, in both adipogenic and osteogenic differentiation processes, NO increased the phosphorylation of JNK/MAPK, and then p-JNK transportation to the nucleus induced the expression of osteogenic transcription factors and repressed the expression of adipogenic transcription factors, thus increasing osteogenesis and reducing adipogenesis.…”
Section: Discussionmentioning
confidence: 89%
“…Moreover, the anti-adipogenesis effect of 6-thioinosine was mediated by decreased expression of PPARγ through JNK pathway. Loss of JNK1 activity resulted in resistance to high-fat diet-induced obesity in vivo [ 50 , 51 ]. In addition, Akt was also essential for inducing PPARγ and adipogenic differentiation; depletion of Akt impaired adipogenesis in mice [ 39 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…PPAR γ is detected in several tissues and it is upregulated by various factors, such as C/EBPs [ 38 , 39 ], estrogen [ 40 ], MEK/ERK signaling [ 41 ], c-Fos [ 42 ], TGF- β [ 43 ], Smad1 [ 44 ], p38 kinase, early growth-response factor-1 (Egr-1) [ 45 ], polyunsaturated fatty acids [ 19 , 46 , 47 ], the orphan nuclear receptor ROR α [ 48 ], the zinc-finger protein Zfp423 [ 49 ], and vitamin E [ 50 ]. Downregulation of PPAR γ is mediated by multiple factors including LPS [ 51 , 52 ], JNK [ 53 55 ], TNF α [ 56 59 ], IL-11 [ 58 ], CCAAT/enhancer-binding protein homologous protein (CHOP) [ 60 ], retinoic acid [ 33 , 61 ], estrogen receptor- (ER-) α [ 62 ], the JAK/STAT pathway [ 23 , 38 , 39 ], interferon-gamma [ 51 , 63 ], leptin [ 64 ], angiotensin II [ 26 ], fasting [ 65 ], and androgens [ 66 ]. Krüppel-like factors (KLFs) have also been shown to affect PPAR γ and lipid metabolism in different ways.…”
Section: Transcriptional Regulation Of Pparsmentioning
confidence: 99%